“Hip-hop é minha bandeira, rap é o hino nacional”: uma análise das transformações estético-políticas do movimento hip-hop brasileiro a partir da Casa do Hip-Hop de Piracicaba - Hummel Hara, Carolina (2022)
This dissertation aims to analyze the aesthetic and political displacements of the hip-hop movement in Brazil through the trajectory of Casa do Hip-Hop de Piracicaba. The empirical field is a prism to approach the processes that cross the urban peripheries in the last decades and the displacements of the national hip-hop movement. The research, of an ethnographic nature, was carried out through interviews, document collection and monitoring of the Casa's social networks. In the construction of the text, rap is configured as the thread that sews the reports and experiences of my interlocutors to the broader dimension of the history of hip-hop and Brazilian urban peripheries.